Risk and Protective Factors Associated With Support of Violent Radicalization: Variations by Geographic Location - B. Heidi Ellis; Alisa B. Miller; Georgios Sideridis; Rochelle Frounfelker; Diana Miconi; Saida Abdi; Farah Aw-Osman; Cecile Rousseau (International Journal of Public Health, 2021)
Objectives: We examine the association between perceived discrimination, mental health, social support, and support for violent radicalization (VR) in young adults from three locations across two countries: Montréal and Toronto, Canada, and Boston, United States. A secondary goal is to test the moderating role of location.Methods: A total of 791 young adults between the ages of 18 and 30, drawn from the Somali Youth longitudinal study and a Canada-based study of college students, participated in the study. We used multivariate linear regression to assess the association between scores on the Radical Intentions Scale (RIS) with demographic characteristics, anxiety, depression, social support, and discrimination.Results: In the full sample, discrimination, age, and gender were associated with RIS scores. When we examined moderation effects by location, RIS scores were associated with depression only in Montréal, and with social support (negatively) and discrimination in Toronto. None of the variables were significant in Boston.Conclusion: These findings suggest that an understanding of risk and protective factors for support of VR may be context-dependent. Further research should take into consideration local/regional differences.